EMPOWERMENT OF PRODUCTIVE ZAKAT FUNDS, SOLUTION FOR SMALL BUSINESS: (Evidence from Badan Amil Zakat Nasional Central Borneo) - Hafizi, Muhammad Riza; Halipah, Nor (Institut Agama Islam Negeri Padangsidimpuan, 2021)
BAZNAS of Palangka Raya is a zakat management institution that is tasked with collecting, distributing and utilizing zakat. This study aims to analyze the optimization of productive zakat utilization in economic empowerment of mustahik, analysis of the benefits of productive zakat in improving the standard of life of mustahik, and analysis of the constraints that BAZNAS feels in optimizing productive zakat.This research is a qualitative type of research using a descriptive qualitative approach. The research subjects were four productive zakat managers and ten informants from mustahik who received revolving fund loan assistance. This research resulted in conclusions, namely, first, the optimization of zakat utilization in the framework of empowering the mustahik in BAZNAS of Palangka Raya through the Palangka Raya Sejahtera program has not been carried out optimally, due to the absence of supervision, assistance and guidance from BAZNAS so that there mustahik who misuse these funds. Second, the benefits of this program are very helpful in the economic empowerment of mustahik with an increase in business results, a network, an increase in family income, and independence. Third, the obstacles that are often felt by BAZNAS in optimizing them are the lack of human resources in management and in the field, the provision of business capital that is misused by mustahik, the lack of trust of muzaki in institutions, and the large number of ZIS collecting organizations besides BAZNAS.